Lifespan and population dynamics of the endemic South American shrimp Artemesia longinaris (Crustacea: Penaeidae) in southeastern Brazil - Antonio L. Castilho (Anais da Academia Brasileira de Ciências, 2015)
The present study investigated the growth, longevity and reproductive dynamics of Artemesia longinaris in the southeastern coast of Brazil over a two-year period. Monthly collections were conducted in Ubatuba and Caraguatatuba using a shrimp fishing boat equipped with “double-rig” nets. Each region was divided into 7 sampling stations up to 35 m deep. Size frequency distributions, growth, longevity, sex ratio, and abundance of individuals in each demographic class, were compared. The relationship between abiotic factors and abundance of each demographic class was assessed using a Canonical Correlation Analysis. A total of 64,641 individuals were collected (6,928 measured) with an estimated longevity of 1.30 (Ubatuba) and 1.14 (Caraguatatuba) years for females and 1.03 years for males in both regions. There was a statistically significant bias in sex ratio toward females (Chi-squared test, p < 0.05) in both regions. The Canonical Correlation Analysis resulted in a canonical correlation coefficient of 0.31 (p = 0.00002). Salinity and temperature showed high correlation mainly with the presence of reproductive females. In general, this demographic class was most common in conditions of low temperature and high salinity. These findings, as well as other studies carried out in colder regions with the same species, are consistent with classical latitudinal paradigm.